2019
DOI: 10.1007/s00405-019-05616-0
|View full text |Cite
|
Sign up to set email alerts
|

Aging effect on sleepiness and apneas severity in patients with obstructive sleep apnea syndrome: a meta-analysis study

Abstract: Different authors have reported that aging could be associated with changes in Obstructive Sleep Apnea (OSA) related parameters (Apnea/hypopnea index, SpO2, reduction of daytime sleepiness, etc.), type of sleep and pattern of collapse. Regarding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
2
18
0
3
Order By: Relevance
“…In the patient group, as expected, the sleep apnea variables were highly correlated, with a high AHI and high BMI predicting a low SpO 2 and increasing age predicting lower sleepiness, SpO 2, and lower subjective nasal obstruction. These findings are in line with previous findings of a positive correlation between AHI and BMI [29] and a negative correlation between BMI and the lowest SpO 2 [30], between AHI and SpO 2 min [31], and between age and ESS scores [32].…”
Section: Discussionsupporting
confidence: 93%
“…In the patient group, as expected, the sleep apnea variables were highly correlated, with a high AHI and high BMI predicting a low SpO 2 and increasing age predicting lower sleepiness, SpO 2, and lower subjective nasal obstruction. These findings are in line with previous findings of a positive correlation between AHI and BMI [29] and a negative correlation between BMI and the lowest SpO 2 [30], between AHI and SpO 2 min [31], and between age and ESS scores [32].…”
Section: Discussionsupporting
confidence: 93%
“…Potentially protective mechanisms show deterioration with age, and the elderly population is therefore more vulnerable to hypoxemia. 44 Increased arousal 45 and decreased slow wave sleep have also been well established 46 In addition, the older population less commonly report daytime sleepiness, 47 whereas younger people with OSA tend to report sleepiness more often. We established the association of more pronounced daytime sleepiness with shorter reaction time in our OSA patients, when age is not controlled for.…”
Section: Discussionmentioning
confidence: 98%
“…We established the association of more pronounced daytime sleepiness with shorter reaction time in our OSA patients, when age is not controlled for. Indeed, it has been reported that OSA has a more prominent effect on daytime sleepiness in young or middle-aged patients than in elderly patients, 47 which might explain the possible moderating effect of age on this relationship. This was additionally confirmed with our results showing the lack of association of daytime sleepiness and psychomotor performance when age was accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…"Obstructive Sleep Apnea (OSA) syndrome is a respiratory sleep disorder characterized by partial or complete recurrent episodes of upper airway collapse, that occurs during the night" [1,2]. OSA manifests with a reduction (hypopnea) or complete cessation (apnea) of airflow in the upper airways [2][3][4].…”
Section: Introductionmentioning
confidence: 99%